Uji Pengaruh Beberapa Herbisida Terhadap Trichoderma sp Secara in Vitro - Muhammad Majid; Hasanuddin Hasanuddin; Mukhtar Iskandar Pinem (Universitas Sumatera Utara, 2014)
In Vitro Test on the Effect of Some Herbicides Application towards Trichoderma sp. This research’sobjective is to study effect of herbicide ingredient with different concentration to growth of myceliumcolony and spore density of Trichoderma sp. Trichoderma sp was inoculated in PDA which havebeen added with six different herbicide ingredients, there are paraquat, glyphosate, fenoxaprop-ethyl,triclopyr, 2,4D, and fluroxypyr at three different concentrations, there are 100%, 75%, and 50% fromrecommended concentration. This research was conducted from May until October 2013 atPhytopathology Laboratory, Agriculture Faculty, University of Sumatera Utara, by using factorialcompletely randomized design with three replications. The result have showed that highest extensiveof mycelium colonywas observed at fluroxypyr 50% concentration, meanwhile the lowest extensive ofmycelium colony was observed at glyphosate 50% concentration. Highest spore density wasobservedat fluroxypyr 50% concentration , meanwhile the lowest spore density was observed at paraquat 100%concentration. Herbicide ingredient interaction with concentration of herbicide very significantlyaffected growth of mycelium colony and spore density of Trichoderma sp.Keywords: Trichodermasp, herbicide, biological agent